NEGARA HUKUM DAN POLITIK HUKUM ISLAM DI INDONESIA: CATATAN KRITIS ATAS PEMIKIRAN NURCHOLISH MADJID - Hidayat, Undang (Asy-Syari'ah, 2016)
Many muslim scholars believed that the idea and model of legal state had exsited since the first hijriya Islamic century ago, when the prophet of Muhammad SAW declared Madina State, including with all instruments and its requirement of the state such as territory, constitution, society, and declaration. This view is also admitted by the Western Scholars who stated that the Prophet of Muhammad SAW had successfully implemented the bases of political authority and the model of the strongly modern state with the spirit of democracy in the past.